Kerjasama Antara Orang Tua Dan Guru Dalam Meningkatkan Prestasi Belajar Siswa Kelas 3-B Di Mi Attanwir Bojonegoro - Robiatul Adawiyah dan Moch. Nurcholis Majid (Pena Islam Jurnal Pendidikan Agama Islam, 2021)
This study discusses the cooperation between parents and teachers in improving student achievement in class 3di MI Attanwir Bojonegoro. Education in the current era of globalization is faced with an increasing number of challenges that must be achieved. In fact, there are various challenges and obstacles that make students, teachers, and parents difficult and unable to achieve the expected learning achievement. In order to face challenges and obstacles to increase achievement. In this study using a qualitative research method with a phenomenological approach. By producing the following findings: conducting routine evaluations once a month, conducting deliberations related to learning achievement, providing private lessons with low learning achievement and involving parents in important events at school.